Glucocorticoid receptors: finding the middle ground - Desmet, Sofie J.; De Bosscher, Karolien (The Journal of Clinical Investigation, 2017)
Glucocorticoids (GCs; referred to clinically as corticosteroids) are steroid hormones with potent anti-inflammatory and immune modulatory profiles. Depending on the context, these hormones can also mediate pro-inflammatory activities, thereby serving as primers of the immune system. Their target receptor, the GC receptor (GR), is a multi-tasking transcription factor, changing its role and function depending on cellular and organismal needs. To get a clearer idea of how to improve the safety profile of GCs, recent studies have investigated the complex mechanisms underlying GR functions. One of the key findings includes both pro- and anti-inflammatory roles of GR, and a future challenge will be to understand how such paradoxical findings can be reconciled and how GR ultimately shifts the balance to a net anti-inflammatory profile. As such, there is consensus that GR deserves a second life as a drug target, with either refined classic GCs or a novel generation of nonsteroidal GR-targeting molecules, to meet the increasing clinical needs of today to treat inflammation and cancer.